Autologous Stem Cell Transplantation in Common Variable Immunodeficiency: A Case of Successful Treatment of Severe Refractory Autoimmune Encephalitis - Froehlich, Matthias; Schwaneck, Eva C.; Gernert, Michael; Gadeholt, Ottar; Strunz, Patrick-Pascal; Morbach, Henner; Tony, Hans-Peter; Schmalzing, Marc (Frontiers in Immunology, 2020)
Common variable immunodeficiency (CVID) is the most common primary immunodeficiency in adults. It is associated with hypogammaglobulinemia, recurring infections and autoimmune phenomena. Treatment includes immunoglobulin substitution and immunosuppressants. Autoimmune neurological manifestations of CVID are rare and occur predominantly as granulomatous disease. We report the case of a 35-year-old woman with CVID who developed autoimmune encephalitis as demonstrated by double cerebral biopsy. Infectious or malignant causes could be excluded. Despite intensive immunosuppressive therapy with common regimens no significant improvement could be achieved. Ultimately, an autologous hematopoietic stem cell transplantation (aHSCT) was performed, resulting in lasting complete remission of the encephalitis. To our knowledge, this is the first report of refractory autoimmune phenomena in CVID treated by aHSCT.